Pre-Service English Teachers’ Voice on Virtual Teaching Practice: Shifting from Face-to-Face Teaching into Virtual Teaching - Fitria Handayani; Iin Widya Lestari; Aprilia Susanti (PT. Global Research Collaboration, 2023)
Pre-service English teachers face various challenges that can significantly impact their competencies and roles, particularly in dealing with students and fellow teachers. The COVID-19 pandemic has added an extra layer of complexity by necessitating the transition from traditional face-to-face learning to online education. This shift is evident in the case of the microteaching course, which originally took place in a physical classroom but was abruptly moved to an online format. This study aims to examine the experiences of pre-service English teachers in virtual teaching practice and how they navigate the challenges associated with professional development during the microteaching course. A total of 31 pre-service English teachers participated in this research, engaging in virtual teaching practice. Data was collected through in-depth interviews, questionnaires, and reflective journals. The findings indicate that pre-service English teachers acknowledge the ineffectiveness of virtual microteaching, citing difficulties in managing and accessing teaching processes as well as the challenges of creating suitable teaching materials. As a result, future pedagogical practices should focus on enhancing the preparation and design of teaching and learning materials to better support the professional development of pre-service English teachers. This will ultimately contribute to their growth as educators during their teaching internships.